2020
DOI: 10.1038/s41467-020-19099-9
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Bayesian reassessment of the epigenetic architecture of complex traits

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…We derive a model that we call BayesRR-RC in Supplementary Note 1 and the “Methods” section, which is based on grouped effects with mixture priors, improving on the formulations of refs. 11 13 . Like these former methods, we consider a spike probability at zero (Dirac delta function), and a scale mixture of Gaussian distributions as a slab probability density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We derive a model that we call BayesRR-RC in Supplementary Note 1 and the “Methods” section, which is based on grouped effects with mixture priors, improving on the formulations of refs. 11 13 . Like these former methods, we consider a spike probability at zero (Dirac delta function), and a scale mixture of Gaussian distributions as a slab probability density.…”
Section: Resultsmentioning
confidence: 99%
“… 16 , 27 it is showed that the former case requires weaker conditions in order to recover the true vector β consistently than the latter. Although the sampling scheme was different, we have shown that a similar model with only two groups: genetic markers and epigenetic markers, is successful in identifying BMI and smoking epigenetic signatures 13 . The baseline model derivations for this model are outlined in Supplementary Note 1 , a BSP Gibbs sampling scheme and an assessment of its performance is outlined in Supplementary Note 2 , and an assessment of the model performance with correlated covariates is outlined in Supplementary Note 4 .…”
Section: Methodsmentioning
confidence: 99%
“…In the study by Langdon et al, 47 methylation scores were evaluated in participants with oropharyngeal cancer and moderately large associations (HR = 1.2‐1.3) with survival were observed for some scores in adjusted models, with modest improvements in terms of prediction. Three other scores were evaluated in that study 10,48,49 as well as just methylation at cg05575921 ( AHRR , smoking), 12 for which the results were similar to those we considered. Other attempts were also made to use individual, or a restricted set of, smoking‐associated methylation marks to predict lung cancer or other smoking‐related outcomes, focusing on the strongest observed associations (eg, AHRR ), for example, in the studies by Baglietto et al including MCCS data, 23 Zhang et al 50,51 and others 52‐55 …”
Section: Discussionmentioning
confidence: 75%
“…This allowed for direct comparisons between protein and EpiScore measures in the context of incident disease analyses, which has only recently been possible owing to the expansion of the cohort’s epigenetic resource. As DNAm may record chronic exposure to a range of environmental risk factors (30) and biological processes such as inflammation (20,31), EpiScores may be reflective of a range of biological pathways that occur upstream of disease diagnoses. Given that GDF15 and Nt-pro-BNP are promising biomarkers for a range of diseases, our EpiScores are well-positioned candidates with many potential use-cases.…”
Section: Discussionmentioning
confidence: 99%
“…The xBayesR+ software implements penalised Bayesian regression on complex traits (30). The BayesR method has been found to outperform linear and mixed model approaches and implicitly adjusts for probe correlations, data structure (such as relatedness) and unobserved confounders (30,32).…”
Section: Methodsmentioning
confidence: 99%